2012
DOI: 10.1186/1746-4269-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Human attitudes towards herpetofauna: The influence of folklore and negative values on the conservation of amphibians and reptiles in Portugal

Abstract: BackgroundHuman values and folklore of wildlife strongly influence the effectiveness of conservation efforts. These values and folklore may also vary with certain demographic characteristics such as gender, age, or education. Reptiles and amphibians are among the least appreciated of vertebrates and are victims of many negative values and wrong ideas resulting from the direct interpretation of folklore. We try to demonstrate how these values and folklore can affect the way people relate to them and also the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 39 publications
8
121
3
15
Order By: Relevance
“…Lower willingness to support animal protection correlates (among other things) with their perceived aesthetic value (Ceríaco, 2012;Gunnthorsdottir, 2001;Knight, 2008;Prokop & Fančovičová, 2013a). Although this variable was not specifically examined in this study, aggressive-looking animals are in all probability perceived as less appealing than the same, but neutral-looking animals.…”
Section: Willingness To Support Animal Protectionmentioning
confidence: 77%
“…Lower willingness to support animal protection correlates (among other things) with their perceived aesthetic value (Ceríaco, 2012;Gunnthorsdottir, 2001;Knight, 2008;Prokop & Fančovičová, 2013a). Although this variable was not specifically examined in this study, aggressive-looking animals are in all probability perceived as less appealing than the same, but neutral-looking animals.…”
Section: Willingness To Support Animal Protectionmentioning
confidence: 77%
“…Percepção ambiental de agricultores Sendo assim, é possivel dizer que atitudes de repulsa para com os anfíbios são, por vezes, controversas e que muitas vezes a influência cultural favorece o comportamento negativo junto à herpetofauna (Ceríaco, 2012). No entanto, o conhecimento das comunidades locais contribui para o acumulo de informações a respeito do manejo destas espécies de repteis e anfibios (Alves e Souto, 2011).…”
Section: Figura 4 -Agroquímicos (Inseticidas E Herbicidas) E Equipameunclassified
“…In their study, the public's attitude to, and knowledge of frogs was poor. A study of Ceriaco (2012), conducted in Portugal, also found that the presence of wrong perceptions and negative values about amphibians and reptiles predicts persecution and anticonservation attitudes. The presence of folklore was related to the presence of negative attitudes.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%